Early Mobility in the Hospital: Lessons Learned from the STRIDE Program - Hastings, Susan Nicole; Choate, Ashley L.; Mahanna, Elizabeth P.; Floegel, Theresa A.; Allen, Kelli D.; Houtven, Courtney H. Van; Wang, Virginia (My University, 2018)
Immobility during hospitalization is widely recognized as a contributor to deconditioning, functional loss, and increased need for institutional post-acute care. Several studies have demonstrated that inpatient walking programs can mitigate some of these negative outcomes, yet hospital mobility programs are not widely available in U.S. hospitals. STRIDE (assiSTed eaRly mobIlity for hospitalizeD older vEterans) is a supervised walking program for hospitalized older adults that fills this important gap in clinical care. This paper describes how STRIDE works and how it is being disseminated to other hospitals using the Replicating Effective Programs (REP) framework. Guided by REP, we define core components of the program and areas where the program can be tailored to better fit the needs and local conditions of its new context (hospital). We describe key adaptations made by four hospitals who have implemented the STRIDE program and discuss lessons learned for successful implementation of hospital mobility programs.
Keywords: mobility; hospitalization; older adults; implementation